2022
DOI: 10.3390/ijerph19031135
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Adherence Behavior Changes during COVID-19 Outbreak in a Portugal Patient Cohort

Abstract: Concerns, behaviours, and beliefs influence how people deal with COVID-19. Understanding the factors influencing adherence behaviour is of utmost importance to develop tailored interventions to increase adherence within this context. Hence, we aimed to understand how COVID-19 affected adherence behaviour in Portugal. A cross-sectional online survey was conducted between 1 March and 3 April 2021. Descriptive statistics were performed, as well as univariable and multivariable regression models. Of the 1202 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
2
7
0
1
Order By: Relevance
“…This does not only prevent them from receiving complete examinations and treatments. This limitation is also deteriorating medication adherence among patients with chronic illness, particularly those with higher psychological stress resulting from the pandemic (9,10). Furthermore, many underinsured patients face a routine drug shortage.…”
Section: Introductionmentioning
confidence: 99%
“…This does not only prevent them from receiving complete examinations and treatments. This limitation is also deteriorating medication adherence among patients with chronic illness, particularly those with higher psychological stress resulting from the pandemic (9,10). Furthermore, many underinsured patients face a routine drug shortage.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a previous study showed no significant difference in adherence to medication between sexes during the pandemic. However, the study examined nonspecific diseases, while our study examined rheumatic autoimmune patients who were predominantly females [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural interventions such as lockdowns, social distancing, and the usage of masks were then implemented, likely decreasing other infections and access to medical appointments. In addition, recommendations from the WHO narrowed antibiotics use [ 17 , 18 , 19 , 20 , 21 ]. These features are considered possible sources of the perceived significant negative growth rates of macrolides (e.g., azithromycin and clarithromycin) and quinolones (e.g., ciprofloxacin), mostly dispensed in ambulatory care.…”
Section: Discussionmentioning
confidence: 99%